2019
DOI: 10.1093/mnras/stz3294
|View full text |Cite
|
Sign up to set email alerts
|

Examining the physical conditions of a warm corona in active galactic nuclei accretion discs

Abstract: A warm corona at the surface of an accretion disc has been proposed as a potential location for producing the soft excess commonly observed in the X-ray spectra of active galactic nuclei (AGNs). In order to fit the observed data the gas must be at temperatures of ∼ 1 keV and have an optical depth of τ T ≈ 10-20. We present one-dimensional calculations of the physical conditions and emitted spectra of a τ T = 10 or 20 gas layer subject to illumination from an X-ray power-law (from above), a blackbody (from belo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…On the other hand, only a few attempts of realistic modelings of the warm corona emission have been done so far (e.g. Ballantyne 2020). At such low temperature (around 1 keV) large atomic opacities could dominate over the Thomson opacities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only a few attempts of realistic modelings of the warm corona emission have been done so far (e.g. Ballantyne 2020). At such low temperature (around 1 keV) large atomic opacities could dominate over the Thomson opacities.…”
Section: Introductionmentioning
confidence: 99%
“…If the soft excess emission is not dominated by disk reflection, the spin measurements inferred from the full band spectra (Walton et al 2013b, Jiang et al 2019c) may indeed disagree with those obtained from the iron line alone (Kara et al 2017, Parker et al 2018, Frederick et al 2018. For example, Ballantyne (2020) has suggested a hybrid model combining a warm corona with disk reflection to explain the soft excess and Jiang et al (2019c) have shown that the warm corona and the high density disk reflection solutions provide equally good fits for the data of Ton S180, so a spectral analysis alone does not seem to be able to select the correct model. The combined analysis of other data, like rms (e.g.…”
Section: Reflection Spectrummentioning
confidence: 98%
“…The degree of reflection Compton-scattering in the corona will scale, of course, with the coronal emission strength, but the precise relationship will depend on disk-coronal geometry. Centrally compact coronae are likely to be less efficient at intercepting disk and disk-reflection emission compared to other disk-hugging planar geometries such as the surface ("warm") corona described by Ballantyne (2020).…”
Section: Comptonized Reflection Componentmentioning
confidence: 99%
See 2 more Smart Citations